itu Pengaruh Penggunaan Media Pembelajaran Instagram Terhadap Hasil Belajar Siswa Dengan Menggunakan Model Discovery Learning Pada Materi Laju Reaksi - Inka Pungky Rahmawati; Sri Yamtinah; Suryadi Budi Utomo; Hayuni Retno Widarti; Ari Syahidul Shidiq (Postgraduate, University of Mataram, 2023)
In Era 4.0, the development of media and learning processes, such as using Instagram as a learning media, is required to make learning more meaningful. This is due to the fact that Instagram is a prominent social media network with over 400 million members. Learning models that can accommodate the skills required in the twenty-first century must be used to make learning more relevant. The discovery learning model is one of them. As a result, this study aims to evaluate the effect of using Instagram learning media on student learning outcomes using the discovery learning model on reaction rate material. A quasi-experimental design was used in this study, with an experimental class of 36 students and a control class of 36 students. This study employed ten multiple-choice questions in the pre-test and post-test to measure student learning outcomes. The N-Gain and Wilcoxon tests were then performed. The study findings demonstrate that employing Instagram learning media using the discovery learning model influences increasing student learning outcomes.